Problem Set 1 Solutions
Problem Set 1 Solutions
Problem Set 1 Solutions
Answer: y ′ is a minimal consumption threshold. Imagine the goods y is food. It is reasonable to assume
you have no real benefits to consume less than the minimum you need to survive. Consuming less is not an
admissible solution of an eventual optimization problem.
y′
x
0
Comment: Note that in the notation y ′ the prime stands to distinguish the point y ′ from y. It has no relation
to a derivative.
2 Exercise: Sets
A consumer’s budget set is
m
B= (x, y) ∈ R2+ : p1 x + p2 y ≤ m + v, x ≤ ,
p1
where p1 , p2 > 0 are prices, m > 0 is income, and v > 0 is good y vouchers. Illustrate this set. Write B as
the union and/or intersection of two well-defined sets.
1
y
m+v
p2
x
m
0 p1
3 Exercise: Functions
Let L(X, Y ) be the vector space of all linear mappings from vector space X to vector space Y . Let T ∈
L(Y, Z), S ∈ L(X, Y ). Show that the composition of the two linear functions, T (S(·)), is linear.
4 Exercise: Functions
Define the notions injectivity, surjectivity, and bijectivity. Discuss these properties for the following functions:
1. f : R+ → R+ , f (x) = x2 ,
2. g : R → R+ , g (x) = x2 ,
3. h : R → R, h (x) = x2 ,
4. h : R → R, h(x) = x3 − x.
Answer:
2
f is surjective (”onto Y ”) if f is a function and its range is the whole set Y , i.e., f (X) = Y .
f is injective (”one-to-one” or ”into”) if it always assigns a different image to different elements of X, i.e., if
x1 ̸= x2 , then f (x1 ) ̸= f (x2 ).
Finally, a function is bijective if it is both surjective and injective. It follows that f is bijective if each element
of Y has an inverse image and the inverse image is unique.
1. The function f is injective and surjective and therefore bijective because if x1 ̸= x2 then f (x1 ) =
2 2 √
(x1 ) ̸= (x2 ) = f (x2 ) since f is monotone increasing on the set R+ . Furthermore, with y = x there
+ +
is a mapping from x ∈ R onto y ∈ R .
2. The function g is surjective for the same reason as above but it is no longer injective because for the
values x1 = 1, x2 = −1 one obtains f (x1 ) = f (x2 ). It is not bijective.
3. Function h is neither injective nor surjective. It is not injective for the same reason as in (b) and it is
not surjective because value y = −1 in the image of h has no corresponding value x in the preimage.
It is not bijective.
4. Function h is surjective, but not injective. Prove by contradiction:
Assume that h is injective, i.e. ∀x1 , x2 s.t. x1 ̸= x2 ⇒ f (x1 ) ̸= f (x2 )
h(x) = 0 ⇒ x3 − x = 0 ⇒ x = 0, x = 1, x = −1
x1 = 0, x2 = 1, x1 ̸= x2 ⇒ f (x1 ) = f (x2 ) = 0 ⇒contradiction⇒ h(x) is non-injective.
It is not bijective.
5 Logic
Negate the statement:
1. For all x, there is y such that for all z : z > x, z > y.
2. ∀x ∈ R, ∃(y, z) ∈ R2 : y < x < z.
3. There is a country in which every citizen has a friend who knows all the constellations.
4. In every village, there is a person who knows everybody else in that village.
Answer:
1. There exists x for which for all y there exists z s.t. z ≤ x or z ≤ y.
2. ∃x ∈ R : ∀(y, z) ∈ R2 , x ⩽ y or x ⩾ z.
3. For all countries in which there exists a citizen has no friend who knows all the constellations.
4. To negate this statement, we will split it into parts and transform them into mathematical statements:
In every village... −→ ∀v ∈ V ,
V being the set of villages.
... there is a person... −→ ∃p ∈ Pv ,
Pv being the set of inhabitants of a village v.
... who knows everybody else in that village → Π(p),
Π(p) being a property of knowing everybody
else in the same village.
Negation:
˜(∀v ∈ V ) −→ ∃v ∈ V −→ There exists a village...
˜(∃p ∈ Pv ) −→ ∀p ∈ Pv −→, ...everybody...
˜Π(p) −→ ˜Π(p) −→ does not know everyone else in the same village.
3
There exists a village where everybody does not know everyone else in the same village. Or in other
words: In at least one village, each person does not know everyone else. Or:
In at least one village, nobody knows everyone else.
6 Exercise: Logic
Let A and B be statements. Suppose the following theorem is true: ”A is true if and only if B is false.”
Which of the following statements follow from this theorem?
1. If A is true, then B is false.
Answer: Equivalence implies: from one statement follows the other (in both directions) and from the
negation of one statement follows negation of the other (in both directions)
A ⇐⇒ ˜B.
As we are studying the implications of the theorem, we presume it is correct, thus we need to look only at
the states in which it is correct.
A B ˜B A ⇒ ˜B A ⇐ ˜B A ⇔ ˜B
T T F F T F
T F T T T T
F T F T T T
F F T T F F
1. True
A B ˜B A ⇒ ˜B A ⇐ ˜B A ⇔ ˜B
T T F F T F
T F T T T T
F T F T T T
F F T T F F
2. True
A B ˜B A ⇒ ˜B A ⇐ ˜B A ⇔ ˜B
T T F F T F
T F T T T T
F T F T T T
F F T T F F
3. True
A B ˜B A ⇒ ˜B A ⇐ ˜B A ⇔ ˜B
T T F F T F
T F T T T T
F T F T T T
F F T T F F